Diversifikasi Mata Pencaharian di Kawasan Wisata Lembanna Tinggimoncong Gowa - Mrs Anisa (Rayhan Intermedia, 2019)
This study aims to find out: To find out how the livelihoods of the Lembanna Village community before the tourist area, know how to diversify their livelihoods from farming to being traders in the Lembanna tourist area and find out how the socio-cultural impact on local communities around the Lembanna tourist area. In this study used a type of qualitative research that was analyzed and written descriptively. The technique of data collection is done by using the method of observation, interviews, and documentation by involving as many as 8 informants. Based on the results of the study, it was shown that: (1) the people in Lembanna village, who used to work as farmers who worked in the garden both on their own and other people, as for the economy when they worked as farmers, namely harvesting in 4 months, then earning income presumably to fulfill the daily needs of children and their families. They planted tomatoes, mustard greens, carrots and various other vegetables. (2) the people in Lembanna village tourist area who decide to trade there are several things or ways they trade, there are 4 things done by traders in the Lembanna village tourism area, which are related to capital and profits, the concept of